(untitled) (Research, Society and Development, 2022)
Building perspectives and approaches for critical mathematics teaching is one of the challenges presented in the teaching work. In this work, we intend to build statements about work possibilities in the teaching of the content of functions from a process of research in a experiment with vegetables, thus boosting the articulation of mathematics to agriculture, building a scenario of potentializing mathematical learning. From a qualitative study, of a basic and exploratory nature, with the main character of a bibliographic review, but not essentially, as a field research was developed, supported by an experiment carried out with Lettuce (Lactuca sativa). Making it possible to produce, collect and mobilize data in modeling processes in the teaching of mathematics, it is possible to invite students to active subjects in their learning through research scenarios. As a proposition, it is pointed out that the study of functions can be worked from the data found in this scenario in a dialogical and critical perspective, fostering the citizen base. This approach contributes to the development of an education that values the subjects, increases their self-esteem, enhancing their learning, understanding that emerges from a training context based on equity and more aligned with social justice.